Einhundert Jahre Deutsches Entomologisches Institut. - Ebert, Werner; Rohlfien, Klaus; Petersen, Günther; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1986)
The contribution gives a survey on the historical development of the German Institute of Entomology by stages according to their aims and tasks by the help of unpublished sources. The most important works about history, rescarch, treating of collection and opening of the library will be mediated.